Cross-Sectional Analysis of Instagram Use in American Plastic Surgery Practices. Issue 6 (27th September 2022) - Sultan, Darren L.; Nazarian, Sheila S.; Furnas, Heather J.; Amalfi, Ashley N.; Perrotti, John; Clappier, Mona; Siddiqui, Sabrina; Suydam, Rebecca; Barnett, Sarah; Tanna, Neil
Abstract : Background: The growth of social media has transformed advertising within plastic surgery. Recent studies have characterized these developments, but objective analysis is needed. Methods: This is a cross-sectional analysis of online media use by American Society of Plastic Surgeons members who received board certification in 2000, 2005, 2010, 2015, or 2019. Online searches and StatShow revealed social media and website metrics. Metropolitan-based practices were determined using Department of Agriculture continuum codes. Descriptive and quantitative analyses were used to make inferences regarding study aims. Results: This study included 811 surgeons. A total of 58.6 percent had practice websites and 43.9 percent had professional Instagram accounts. Instagram use was widespread across subspecialties and there was no significant difference in the number of followers by subspecialty ( p = 0.34). Year of certification had no significant effect on the number of followers ( p = 0.12); however, recently certified and seasoned members had the fewest. The top 1 percent of surgeons had more followers than the remaining 99 percent combined. Those with metropolitan-based practices had significantly higher website traffic ( p = 0.01) but no difference in the number of followers ( p = 0.88). There was no evidence that the number of followers or posts per month correlated with website traffic ( R 2 = 0.004 and 0.036, respectively). Conclusions: The study demonstrates findings from a cross-sectional analysis of plastic surgeons from different training backgrounds, regions, and tenure. The use of Instagram in professional practice is widespread but there is no correlation between its use and increased website traffic.